Action-research in the development of critical thinking and change of attitude towards knowledge: An experience in the Epistemology lectureship of the doctoral program in Education - Benavides Vía, Gloria (2020)
The present study aims to analyze the methodology of teaching the subject of Epistemology in a doctoral program in Education, using an educational method based on action research. It constitutes an exploratory research, of mixed approach, fundamentally qualitative with phenomenological and hermeneutic orientation, it is of an applicative level, quasi-experimental type, to the extent that a program based on the action-research methodology is applied, and on the other hand it is quantitative to the extent that a test that evaluates critical thinking at the beginning and at the end of the development of the subject was applied. It was tried to demonstrate that such methodological procedure favors the change of disposition towards critical thinking of doctoral students, since it develops more confidence in reason, demonstrating a mental amplitude and curiosity about the subject, obtaining a better handling of information and are oriented to the search for the truth, demonstrating that attitudes towards knowledge remain constant.